The Use of Photography in Teaching and Learning in Tanzanian Pre-Primary Education - Ignasia Mligo (CV. Samuel Manurung and Co, 2024)
The purpose of this study was to investigate the relevance of using photography in Tanzanian Pre-Primary Education learning context. Experience showed that pre-primary teachers lacked knowledge of the importance of photography in teaching and learning to young children. Constructivism theory underpinned the study. As young children learn by using photography, they experience the world and reflect upon those experiences. So, they build their own representations and incorporate new information into their pre-existing knowledge. This qualitative study employs a case study design. A total of 24 study informants participated in the study; 11 were males and 13 were females, whereby 18 were pre-primary children and six (06) were pre-primary teachers. Data were collected through interviews; classroom observation and documentary reviews where thematic analysis were conducted using various constructs. The study revealed that using photography as teaching approach made classroom active, it enables children to develop their own ideas, creativity, inquisitiveness, and well engaged. Thus, enhancing their own interpersonal skills while at the same time enquiring the authenticity and relevance of the concepts at hand. The situation was different from what happened before teaching by using photography where children were passive and take in information from teachers. The study recommends that teaching and learning through photography as an approach should be integrated in the pre-primary curriculum. Also, government policy makers should take into consideration the use of photography in schools to enhance teaching and learning activities.